Design and Development of Tourism Geographical Information System of Semarang City Based On Android Mobile - Shobirin, Achmad; Aryotejo, Guruh; Danang, Danang (Universitas PGRI Semarang, 2020)
The development of information technology that exists today is very rapid, making us to keep abreast of the development of these technologies. Technology is able to present all information quickly and instantly, leaving old patterns such as gathering information manually which may require more time. Information technology today is very effective and efficient as indicated by the speed of processing time and the accuracy of the information needed. One of them is the information about tourist attractions, which is currently increasingly in demand by people who want to vacation with friends, relatives and family. However, the lack of information about the location of attractions that want to be visited, especially for potential tourists from outside the area of Semarang, make the author interested in design and creating the Semarang City Geographic Tourism Information System Based on Android Mobile to facilitate the search for the nearest route to the desired tourist attraction. The method used is using the Geographic Information System based on the data from the Semarang City Culture and Tourism Service. The Semarang City Tourism Geographic Information System Based on Android Mobile is a solution to problem solving as a medium to obtain information and tourism locations in the Semarang, which is applied in Android Smartphone devices, especially for the people from outside the city of Semarang.Â